B-5-2 NIRSデータを用いた運動とイメージのネットワーク解析(感覚処理(2)) - 須貝, 雅子; 安達, 雅春 (バイオメディカル・ファジィ・システム学会大会講演論文集, 2012)
NIRS(Near infra-red spectroscopy) is the spectroscopic device with which the brain activity can be measured non-invasively and easily. In this study, the functional connectivity in NIRS data is analyzed by means of recurrence plot. Eleven normal subjects (all of them are right-handed) participated in the examination. In motor imagery task, some of the edges as functional connectivity are significantly larger compared to the rest. On the other hand, no significant difference is found in functional connectivity in motor execution. It is demonstrated that recurrence plot is a useful tool for detecting state transition in time series, so the results of this study could contribute the decoding and BCI.